Incidence of consumption and brands in subjective well-being experience among young people: a qualitative exploration - Vargas Bianchi, Lizardo (2019)
Research shows that consumption correlates with the experience of subjective well-being. However, there is little literature on this phenomenon among young people. This exploratory study aims to know how university students perceive that consumption and brands intervene on subjective well-being and identify the elements they consider in their consumption behaviors aimed at obtaining well-being. A qualitative methodology of phenomenological design was used, with university students from the city of Lima. The analysis followed a process of descriptive coding. The experience of consumption and well-being reveals itself as a phenomenon relative to each person, in particular their sense of need and value framework about material goods, factors that seem to be modulated by their family environment. Young people find in purchase practices and brands a conduit to meet their social needs, specifically belonging and acceptance in groups.